Marketing Strategy in Dental Practices: A Scoping Review Study - Mita Juliawati; Marta Juslily; Khalda Fathiah; Laura Emily; Thomas Aurelius; Jessica Budiono (Journal of Indonesian Dental Association, 2023)
Introduction: Knowledge and skills required for a dentist to be able to manage dan promote their dental practice are not only clinical skills but also managerial skills. One of which is the marketing and its strategy. Marketing need to be implemented in dental services. Objective: To determine the marketing strategies in dental services. Method: The research design used for this manuscript is literature the review. The selection criteria for the articles are experimental and cross-sectional studies. Articles were obtained using electronic databases Google Scholar with the keywords "dental services marketing" AND "marketing strategy" AND "advertising in dentistry" AND "dental practices" AND "dentist patient" AND "social marketing" AND "marketing platform" AND "social media or twitter or instagram or facebook or websiteâ€. Result: A total of 367 articles were identified after screening and removing duplicates, 11 journals met the inclusion criteria. These studies mainly covered the field of dental education and research on marketing strategies through social media in various countries. Conclusion: Social media is one effective marketing strategy in attracting patients to come to dental clinics. However, in some studies, social media is considered to have less influence on patients' considerations choosing a dentist. Social media platforms preferred by dentists as marketing platforms are LinkedIn, Facebook, Instagram, Twitter, and WhatsApp. One critical issue in the use of social media is related to ethical and privacy perspectives.